PENGARUH KUALITAS PELAYANAN DAN PENETAPAN HARGA TERHADAP MINAT BELI KONSUMEN PADA TOKO AKSESORIS SIANOK MOTOR DURI - Anugrah Bima Ferdiantama; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research was conducted at the Sianok Motor Duri Accessories Store, which is located at Jalan Jenderal Sudirman No. 64, Balik Alam, Mandau District, Bengkalis Regency, Riau. This study aims to determine the effect of research quality and pricing on consumer buying interest partially and simultaneously. This research uses quantitative descriptive analysis method with SPSS program. The population in this study were all consumers at the Sianok Motor Duri Accessories Store in 2019 as many as 812 and the sample from this study as many as 89 respondents from consumers of the Sianok Motor Duri Accessories Store. Determination of the sample in this study using the Slovin formula, namely by nonprobability sampling technique with accidental sampling technique. Data analysis uses validity test, reliability test, simple linear analysis, multiple linear analysis, determination analysis and significance test with t test (partial test) F test (simultaneous test). The results of this study indicate the results of the t-test hypothesis of service quality on consumer buying interest, namely t count (8.782)> t table (1.987) meaning that service quality is significant to consumer buying interest. Second, pricing on consumer buying interest is t count (7.277)>t table (1.987) meaning that the price setting is significant to consumer buying interest. F test results of service quality and pricing on consumer buying interest are F count (38.339)>F table (3.10). Keywords: Service Quality, Pricing, Consumer Purchase Interest